2019
DOI: 10.1002/pros.23932
|View full text |Cite
|
Sign up to set email alerts
|

The ternary complex factor protein ELK1 is an independent prognosticator of disease recurrence in prostate cancer

Abstract: Background: Both hormone sensitive and castration-and enzalutamide-resistant prostate cancers (PCa) depend on the ternary complex factor (TCF) protein ELK1 to serve as a This is the author manuscript accepted for publication and undergone full peer review but has not been through the copyediting, typesetting, pagination and proofreading process, which may lead to differences between this version and the Version of Record. Please cite this article as

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 46 publications
0
8
0
Order By: Relevance
“…Moreover, expression of a hypo-ubiquitinated ELK-1 mutant, but not wild-type ELK-1, partially rescued the proliferation defect caused by USP17 depletion in HEK293T cells, illustrating the contribution of this mechanism towards mitogen signalling [ 86 ]. The established role for ELK-1 as an AR tethering element suggests that further studies are warranted to decipher whether USP17 acts on ELK-1 to promote tumorigenesis in PCa [ 91 , 92 , 93 ].…”
Section: Tcfs Showcase Mono-ubiquitination As a Non-destructive Mode Of Repressionmentioning
confidence: 99%
“…Moreover, expression of a hypo-ubiquitinated ELK-1 mutant, but not wild-type ELK-1, partially rescued the proliferation defect caused by USP17 depletion in HEK293T cells, illustrating the contribution of this mechanism towards mitogen signalling [ 86 ]. The established role for ELK-1 as an AR tethering element suggests that further studies are warranted to decipher whether USP17 acts on ELK-1 to promote tumorigenesis in PCa [ 91 , 92 , 93 ].…”
Section: Tcfs Showcase Mono-ubiquitination As a Non-destructive Mode Of Repressionmentioning
confidence: 99%
“…However, we have identified another PEA3 subfamily member, ETV1, to be expressed at high levels in low-grade glioma and decrease in expression in higher grades ( Figure 2 ). ELK-1 protein is known to be a critical partner for the androgen receptor (AR) in prostate cancer, and its expression was found to be associated with a higher clinical stage and prognostic marker of disease recurrence in prostate cancer [ 14 ]. No such distinction was apparent in our study on glioma grades 2–4.…”
Section: Discussionmentioning
confidence: 99%
“…T417 phosphorylation of Elk-1, a member of the ternary complex factor (TCF) subfamily, was found to be associated with the differentiation grade of colonic adenocarcinomas [ 13 ]. Additionally, in high clinical stage prostate cancer, ELK-1, not TCF members ELK3 or ELK4, was found to be associated with disease recurrence [ 14 ]. In fact, ELK1 expression was reported to be higher than ELK3 in many cancer cell lines, including brain, skin, and myeloid tumors and sarcomas [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Phosphorylation of Elk-1 through MAPK/ERK signaling pathways activate TCF with serum response factor (SRF) and serum response elements to induce target gene transcription. Various studies showed that prostate cancer was influenced by Elk-1, before and after castration therapy [22], [23], [24]. The study of Patki et al reported that cooperative action of Elk-1 and AR did not involve phosphorylation of Elk-1, did not require SRF, and did not activate TCF.…”
Section: Discussionmentioning
confidence: 99%
“…Elk-1 was an independent risk factor for recurrence of prostate cancer along with clinical T-stage and prognostic grade. It warrants further detailed studies of the clinical utility of including Elk-1 with the currently used predictive signature of disease recurrence in prostate cancer [24]. Kawahara et al found the different result that no statistically significant correlation between p-Elk-1 expression and tumor grade (p = 0.810), but there was a trend toward significance between moderate-strong p-Elk-1 expression and worse patients outcomes [20].…”
Section: Discussionmentioning
confidence: 99%